The Influence of School Climate And Self Regulated Learning Towards Student Engagement in SMA Raksana Medan - Parlindungan Parama Hutagalung, Budi; Milfayetty, Sri; Sari Dewi, Salamiah (International Journal of Educational Research & Social Sciences, 2025)
Student engagement in their school includes cognitive, behavioral and emotional dimensions. At Raksana Medan High School, it can be seen that student engagement in learning is still low. This can be seen from the fact that there are still many students who are still holding devices during the learning process, so that the level of focus and self-regulation in learning decreases. This research aims to see the influence of School Climate and Self Regulated Learning on student engagement at Raksana High School Medan. This research method uses quantitative with a sample size of 175 students. The research results show that there is a significant influence on school climate, self- regulated learning with student engagement seen from the coefficient of determination (R2) = 54.9% with a p value = 0.000 < 0.50. This means that the emergence of student engagement is influenced by school climate and self-regulated learning with a contribution of 54.9%.